Judo for elite Brazilian women: A successful trajectory into the 21st century: A narrative review - Da Silva, Luvanor Santana; De Lima, Denis Medeiros; Barbosa, Francisco de Assis Fernandes; De Lima, Oberdan Floriano; De Almeida, Marcelus Brito (Open Science Journal, 2023)
Background: The objective of this study was to verify, in a perspective way, the history and evolution of the development of the Brazilian Elite Female Judo. Brazilian women's Judo is one of the best Judo teams in the world. Performance and achievement in Olympic and world championships has reached a significant and expressive increase. That is, of course, medal winnings at different competitive levels. Making it one of the most prestigious sport in Brazil. Methods: This is a Narrative Review study, where the Scielo, Google Scholar and PubMed databases were used, with no initial period restriction until the year 2022. Results: Women's Brazilian Judo evolved both individually and as a team. Achieving expressive results in national and international competitions, in the Olympic Games and World Championships. In addition, these results have raised the competitive level of the Brazilian judo team worldwide. It has solidified women within sport and combat sports. However, some barriers (social resistance, lack of investment, little credibility and social representation) persist, albeit with less intensity. Conclusion: We conclude that Brazilian Women's Judo is a strong representative in the competitive, social and world scenario. In addition, that the participation of women raised the sport to a high level of social representation.